Introduction to the Musical Composition “Windu Sara” | Pengantar Karya Komposisi Karawitan “Windu Sara” - I Putu Restu Krisna Arimbawa; I Ketut Partha (GHURNITA: Jurnal Seni Karawitan, 2022)
This musical work with the theme Windu sara is unique in terms of the red color which is quite strong. The red color on this stone has the meaning of unification to society and can cause happiness.